The Contribution of SPECT/CT Bone Scintigraphy in the Localization of an Infective (Purulent) Sacroiliitis – A Case Report - Manevska, Nevena; Popovski, Neron; Makazlieva, Tanja; Popovska, Hristina; Pesevska-Todorcevska, Aleksandra; Stojanoski, Sinisa (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Infectious sacroiliitis (ISI) is an inflammation of one or both of the sacroiliac (SI) joints, relatively rare disorder, affecting between 1% and 2% of all patients with septic arthritis. The variety of symptom presentation makes the diagnosis quite challenging. Combination of laboratory hematological tests, together with diagnostic imaging tools, such as magnetic resonance imaging (MRI), computed tomography (CT), and bone scan (BS), as well as microbiological tests contribute the final diagnosis, which may take up to several months. CASE REPORT: We present a case of a 33-year-old male patient with a history of lower back pain with propagation of the pain in the right leg, accompanied by febrility and hematuria. Laboratory tests showed high values of C-reactive protein, high degradation products and hyperkalemia, leading to a diagnose of acute renal failure stage 3. MRI of the lower spine and pelvis revealed hetero- signal change more to the right where the spinal canal was expanded, accumulating contrast and involved the caudate and the right radix. Тhe displayed sequences were accompanied by an altered morphology of the spinal musculature, with intense accumulation of contrast in parts of the muscle. Paravertebral abscess was detected in the intercaudal and iliac muscles, along with inflammatory edema of the right SI with a suspicion of a sacroiliitis. One week after, a three phase BS showed positive accumulation in the right SI joint in all three phases. The SI index for the right SI joint was 2.09, while for the left SI joint was 1.125. The patient underwent surgical intervention for drainage of the paravertebral abscess. CONCLUSION: The condition of ISI may be sometimes very difficult to be recognized in many patients. Considering the diversity of the clinical manifestations, it is of great importance to select the right imaging modality. The nuclear medicine technique triple phase bone and the hybrid imaging SPECT/CT have been suggested to improve the sensitivity and specificity of the bone scan, providing better characterization of equivocal lesions, especially in the acute form for disease localization.